Minimization Of Entrance Surface Dose And Critical Organ Dose For Medical Radiography Using Optimization Procedures - Nassab Rabor, Lotf Ali Mehdipour (2010)

(untitled)
In hospitals, clinics, nursing homes, and medical laboratories, diagnostic radiography is extensively used to view internal structures of a patient and to aid radiologists and doctors diagnose and treat illness and injury. The most common medical radiography is by passing x-rays through the body and captures the image of the patient by means of a sensitized film. This radiographic procedure must feature the system of dose optimization and limitation known as the practice of ALARA (as low as reasonably achievable) recommended by the International Commission on Radiological Protection. The measurements of the entrance surface dose (ESD) and the critical organ dose (COD) in common medical radiography are very important to ensure the dose limit received by the patient in a single radiographic exposure must fulfill the ALARA principle. The most useful way to evaluate ESD is either by indirect measurement on a phantom using an ionization chamber or thermo luminescent dosimeter (TLD) or using calculation based on mathematical model.